Microsatellite loci reveal heterozygosis and population structure in the critically endangered southern river terrapin (Batagur affinis ssp.) of Peninsular Malaysia+ - Mohd Salleh, Mohd Hairul; Esa, Yuzine (MDPI AG, 2022)
These freshwater turtles are found across Indochina, mostly in large rivers. There is a lack of genetic research concentrating on Malaysia’s southern river terrapin (Batagur affinis) population. We used minimally intrusive methods to collect blood samples from a total of 80 individuals in four different sites in peninsular Malaysia. The genetic difference within and between locations was examined using five microsatellite loci. Our findings indicated that each locus was polymorphic. High numbers of heterozygotes were observed when the percentage of alleles in each locus was compared. Pairwise FST and Nei matrixes revealed considerable genetic differences across individuals from distinct geographical locations. Our population structure analysis shows a significant proportion of assigned individuals are linked to certain collection locations.